RNA G-quadruplex forming regions from SARS-2, SARS-1 and MERS coronoviruses - Kabbara, Amani; Vialet, Brune; Marquevielle, Julien; Bonnafous, Pierre; Mackereth, Cameron D.; Amrane, Samir (Frontiers in Chemistry, 2022)
COVID-19 (Corona Virus Disease 2019), SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome) are infectious diseases each caused by coronavirus outbreaks. Small molecules and other therapeutics are rapidly being developed to treat these diseases, but the threat of new variants and outbreaks argue for the identification of additional viral targets. Here we identify regions in each of the three coronavirus genomes that are able to form G-quadruplex (G4) structures. G4s are structures formed by DNA or RNA with a core of two or more stacked planes of guanosine tetrads. In recent years, numerous DNA and RNA G4s have emerged as promising pharmacological targets for the treatment of cancer and viral infection. We use a combination of bioinformatics and biophysical approaches to identify conserved RNA G4 regions from the ORF1A and S sequences of SARS-CoV, SARS-CoV-2 and MERS-CoV. Although a general depletion of G4-forming regions is observed in coronaviridae, the preservation of these selected G4 sequences support a significance in viral replication. Targeting these RNA structures may represent a new antiviral strategy against these viruses distinct from current approaches that target viral proteins.